Reactive Oxygen Species in the Adverse Outcome Pathway Framework: Toward Creation of Harmonized Consensus Key Events - Tanabe, Shihori; O’Brien, Jason; Tollefsen, Knut Erik; Kim, Youngjun; Chauhan, Vinita; Yauk, Carole; Huliganga, Elizabeth; Rudel, Ruthann A.; Kay, Jennifer E.; Helm, Jessica S.; Beaton, Danielle; Filipovska, Julija; et al. (Frontiers in Toxicology, 2022)
Reactive oxygen species (ROS) and reactive nitrogen species (RNS) are formed as a result of natural cellular processes, intracellular signaling, or as adverse responses associated with diseases or exposure to oxidizing chemical and non-chemical stressors. The action of ROS and RNS, collectively referred to as reactive oxygen and nitrogen species (RONS), has recently become highly relevant in a number of adverse outcome pathways (AOPs) that capture, organize, evaluate and portray causal relationships pertinent to adversity or disease progression. RONS can potentially act as a key event (KE) in the cascade of responses leading to an adverse outcome (AO) within such AOPs, but are also known to modulate responses of events along the AOP continuum without being an AOP event itself. A substantial discussion has therefore been undertaken in a series of workshops named “Mystery or ROS” to elucidate the role of RONS in disease and adverse effects associated with exposure to stressors such as nanoparticles, chemical, and ionizing and non-ionizing radiation. This review introduces the background for RONS production, reflects on the direct and indirect effects of RONS, addresses the diversity of terminology used in different fields of research, and provides guidance for developing a harmonized approach for defining a common event terminology within the AOP developer community.